Manajemen Risiko Produksi pada Usaha Peternakan Sapi Perah Menggunakan Metode Terintergrasi House of Risk (HOR) - Muhammad Arya Andhika Witjaksono, Raden; Widodo, Erwin (Jurnal GeoEkonomi, 2026)
The dairy farming sector plays a crucial role in ensuring food security, yet its operations face multiple interconnected risks that threaten production stability and supply chain continuity. Despite existing risk management efforts, practices are largely reactive and fragmented, with limited systematic prioritization of critical risk sources, resulting in reduced resilience and decision-making effectiveness, particularly in smallholder cooperative systems. This study addresses this gap by developing a proactive and structured risk management framework that integrates the SCOR and House of Risk (HOR) methods. Using a mixed-method approach, data were collected from cooperative dairy farmers and stakeholders through interviews, questionnaires, and Focus Group Discussions, complemented by quantitative analysis of risk events, risk agents, and Aggregate Risk Potential (ARP). The findings reveal that key risks are concentrated in planning, sourcing, and production stages, primarily related to sanitation practices, facility conditions, and operational management. Mitigation strategies emphasizing consistent SOP implementation, enhanced sanitation, adequate infrastructure, and strengthened cooperative involvement were identified as the most effective actions. These strategies are expected to improve operational efficiency, reduce disruptions and contamination risks, maintain milk quality, and promote sustainable farm management. Overall, the study provides actionable insights for proactive risk mitigation and offers a decision-oriented framework applicable to smallholder dairy supply chains.